El silencio femenino en el mito griego de Casandra - Álvarez Espinoza, Nazira (2014)
The purpose of this paper is to study the presence of the rethoric of silence in the mythological feminine models, in specific the character of Kassandra, the Troian princess, in the mythic context of the ancient Greek society. Kassandra speaks inspired by the god Apollo and also by herself. Nevertheless, her voice is silenced, her prophecies are not believed and her discourse is ignored by the society in which she lives. The Troian princess ends her life isolated and surrounded by silence.